Phytochemicals as Immunomodulatory Molecules in Cancer Therapeutics - Sandeep Paudel; Neha Mishra; Rajesh Agarwal (MDPI AG, 2023)
Phytochemicals are natural plant-derived products that provide significant nutrition, essential biomolecules, and flavor as part of our diet. They have long been known to confer protection against several diseases via their anti-inflammatory, immune-regulatory, anti-microbial, and several other properties. Deciphering the role of phytochemicals in the prevention, inhibition, and treatment of cancer-unrestrained cell proliferation due to the loss of tight regulation on cell growth and replication-has been the focus of recent research. Particularly, the immunomodulatory role of phytochemicals, which is pivotal in unchecked cell proliferation and metastasis, has recently been studied extensively. The immune system is a critical component of the tumor microenvironment, and it plays essential roles in both preventing and promoting oncogenesis. Immunomodulation includes stimulation, amplification, or inactivation of some stage(s) of the immune response. Phytochemicals and their products have demonstrated immune regulation, such as macrophage migration, nitric oxide synthase inhibition, lymphocyte, T-cell, and cytokine stimulation, natural killer cell augmentation, and NFκB, TNF, and apoptosis regulation. There is a dearth of extensive accounts of the immunomodulatory effects of phytochemicals in cancer; thus, we have compiled these effects with mechanistic aspects of dietary phytochemicals in cancer, highlighting promising candidates and ongoing clinical trials on immunotherapeutic strategies to mitigate oncogenesis.